Ps--Connected Spaces - Shareef, Hardi A.; Aziz, Hardi N.; Darwesh, Halgwrd M. (Sulaimani Journal for Pure and Applied Sciences, 2015)
The aim of this work is to introduce a new generalization of a pre-connected space, which is called -connected space and study relationship with other types of connected spaces and gives some results on it. Further results concerning preservation of this connectedness like properties under surjections are obtained.
Keywords: Psopen set separated sets connected spaces